1984
DOI: 10.1128/aem.47.6.1343-1345.1984
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition by 2-Bromoethanesulfonate of Methanogenesis from Acetate in a Thermophilic Anaerobic Digestor

Abstract: The effects of 2-bromoethanesulfonate, an inhibitor of methanogenesis, on metabolism in sludge from a thermophilic (58°C) anaerobic digestor were studied. It was found from short-term experiments that 1 ,umol of 2-bromoethanesulfonate per ml completely inhibited methanogenesis from '4CH3COO7, whereas 50 p.mol/ml was required for complete inhibition of l4co. reduction. When 1 p.mol of 2-bromoethanesulfonate per ml was added to actively metabolizing sludge which was then incubated for 24 h. it caused a 60% reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(61 citation statements)
references
References 10 publications
3
58
0
Order By: Relevance
“…In the non-inhibited cul- In the presence of 2-bromoethanesulfonate, more acetate and less methane was formed than in non-inhibited cultures. The fermentation balance was shifted to the overall equations: These shifts in the fermentation balance indicate that bromoethane sulfonate inhibited the acetatecleaving methane bacteria more effectively than the hydrogen-oxidizing bacteria [20]. In hydroquinone-degrading cultures, some phenol accumulated in cultures with high bromoethane sulfonate additions.…”
Section: Stoichiometry and Chemistry Of Substrate Degradationmentioning
confidence: 99%
“…In the non-inhibited cul- In the presence of 2-bromoethanesulfonate, more acetate and less methane was formed than in non-inhibited cultures. The fermentation balance was shifted to the overall equations: These shifts in the fermentation balance indicate that bromoethane sulfonate inhibited the acetatecleaving methane bacteria more effectively than the hydrogen-oxidizing bacteria [20]. In hydroquinone-degrading cultures, some phenol accumulated in cultures with high bromoethane sulfonate additions.…”
Section: Stoichiometry and Chemistry Of Substrate Degradationmentioning
confidence: 99%
“…Compounds that inhibit methanogenesis have been important in research to study pure cultures of methanogens (Ungerfeld et al 2004;Watkins et al 2012), carbon cycling in soils (Sugimoto and Wada 1993;Wu et al 2001), ruminal methanogens (Ungerfeld et al 2006;Zhou et al 2011b), dechlorination (Perkins et al 1994;Chiu and Lee 2001), mercury methylation (Han et al 2010;Avramescu et al 2011), production of volatile fatty acids (Zhang et al 2013;Jung et al 2015), anaerobic digestion (Zinder et al 1984;Navarro et al 2014), and the degradation of nitrosamines (Tezel et al 2011) and methanethiol (Sun et al 2015). Further, inhibitors have been useful in elucidating the activity of methanogens related to metal and metalloid methylation (Meyer et al 2008; Thomas et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important given that a wide diversity of methanogenic inhibitors with varying properties and mechanisms of action are available. Methanogenic inhibitors can be divided into several categories (as reviewed by (Liu et al 2011)), including analogs of coenzyme M (Gunsalus et al 1978;Zinder et al 1984), inhibitors of methanopterin biosynthesis (Dumitru et al 2003), medium-and long-chain fatty acids (Prins et al 1972;Soliva et al 2003), nitrocompounds (Zhou et al 2011b), halogenated hydrocarbons (Denman et al 2007), ethylene (Oremland and Taylor 1975), acetylene (Oremland and Taylor 1975;Sprott et al 1982), and unsaturated analogs of propionate and butyrate (Ungerfeld et al 2003(Ungerfeld et al , 2004(Ungerfeld et al , 2006Zhou et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…The current laboratory-scale study demonstrated that 1-g L −1 slurry (and perhaps lower) rates of Na 2 S 2 O 8 could significantly reduce CH 4 production when compared with untreated slurries. The highest rate (9 g L −1 slurry) of Na 2 S 2 O 8 tested had almost similar effects to 0.05 mole L −1 slurry of BES, a known inhibitor that can stop both the hydrogenotrophic and aceticlastic methanogenesis (Zinder et al, 1984). Despite its impressive effect in mitigating CH 4 production, BES is highly expensive (e.g., US$0.92 for 1 g L −1 slurry) when compared with the chemical oxidants (e.g., <US$0.06 for 1 g L −1 of Na 2 S 2 O 8 or KMnO 4 ) (ebiochem, China).…”
Section: Discussionmentioning
confidence: 76%
“…By including Na 2 S 2 O 8 (98%, Fisher Scientific), the current incubation experiment was set using different rates (R1 = 1, R2 = 3, R3 = 6, or R4 = 9 g or mL L −1 slurry) of KMnO 4 , Na 2 S 2 O 8 , 3% NaOCl, or their combinations (1:1:1, g, g, mL) to assess potential impacts on the abundance of methanogens and bacteria in stored liquid dairy manure. In addition to untreated manure (negative control), manure treated with 0.05 mol L −1 sodium 2-bromoethanesulfonate (BES) (98%, Sigma-Aldrich), which is known to stop both hydrogenotrophic and aceticlastic methanogenesis (Zinder et al, 1984), was used as a positive control. As a reference point, an acidification treatment was also included.…”
Section: Experimental Design and Manure Samplingmentioning
confidence: 99%